FRI0339 Systematic review of drug trials in the treatment of giant cell arteritis. (23rd January 2014) - Yates, M.; Loke, Y.; Watts, R.; MacGregor, A.
Abstract : Background: Giant cell arteritis is the most common vasculitis in individuals aged greater than 50yrs in the western world and has significant morbidity. It is a medical emergency with up to 20% of patients suffering with visual loss. Treatment with high dose glucocorticoids (GC) is the mainstay of treatment. Several other agents have been tried as adjuncts to GC in the treatment of GCA. Objectives: The objective was to conduct a meta-analysis of these therapies to ascertain their benefit over GC regimens. Methods: MEDLINE, CENTRAL and EMBASE searches were used to identify randomised control trials and large observational studies on the treatment of GCA with GC. Searches were carried out independently by two researchers (MY and YL) to date 7 th January 2013. Trials or observational studies were included if more than 20 patients were recruited into each arm of the trial, there was clear criteria for the diagnosis of GCA and did not include patients with exclusively with a diagnosis of PMR. The study was also required to be carried out on humans greater than 55yrs of age and the length of follow-up was at least 6 months. Exclusion criteria consisted of; not reporting of initial dose of GC; or not reporting total cumulative dose; or there were no recorded outcomes of patients. Results: The combined MEDLINE, CENTRAL and EMBASE searches retrieved 3804 articles. Of these only 36 met primary inclusion criteria. 15 of these studies reported some information about the GC regimen used and were included in the qualitative analysis. Only nine of these were of sufficient quality to be included in the meta-analysis. Together these comprised of 568 participants of which 72% were female and had a mean age of 73years. 84% had a positive temporal artery biopsy. Initial starting steroid dose equivalent to prednisolone ranged from 10mg to 1000mg with duration of therapy ranging 26 to 94 weeks. Forrest plots were constructed to assess for advantage of intervention over control arm with pooled estimates if more than one study was available for a specified adjunct (advantage towards control resulted in a RR <1.0 and advantage to control RR >1.0). Three studies compared various GC regimens, with two comparing IV GCs (RR = 0.78 95% CI = 0.54 to 1.12). Another three used methotrexate as an adjunct agent (RR = 0.85 95% CI = 0.66 to 1.11). The remaining three trials compared prednisolone to dapsone, infliximab and hydroxychloroquine. No GC regimen with an adjunct agent was shown to have consistent advantage over oral GC alone. Conclusions: The results from this meta-analysis show that there is no benefit from adjunct agents in terms of efficacy or toxicity. Given the relatively large differences seen in the trials with regard to rate of withdrawal and study duration of GCs, has a bearing on relapse rate. Studies of appropriate power and duration are needed to answer these questions. Disclosure of Interest : None Declared